Assessing the Risk of Antibiotic Residues in Milk Produced in the Republic of Armenia - Pipoyan, D. A.; Beglaryan, M. R.; Gharibyan, G. K.; Aghababyan, A. A. (ՀԱԱՀ հիմնադրամ)
This research sets out to assess both the antibiotic exposure via milk produced in the Republic of Armenia and the associated human health risks. As established, the milk of domestic production contains residual antibiotics (streptomycin, chloramphenicol, tetracyclines). The estimated daily intake (EDI) and the margin of exposure (MOE) for the antibiotics identified upon this research were assessed. It has been indicated that for the population of Yerevan, the daily intake of antibiotics via milk does not exceed the acceptable daily intake (ADI). Moreover, the derived MOE values point to the absence of health risks associated with shop-bought milk.
Keywords: Food Science and Technology